Landscape of CDKN1B Mutations in Luminal Breast Cancer and Other Hormone-Driven Human Tumors - Cusan, Martina; Mungo, Giorgia; De Marco Zompit, Mara; Segatto, Ilenia; Belletti, Barbara; Baldassarre, Gustavo (Frontiers in Endocrinology, 2018)
The CDKN1B gene encodes for the p27Kip1 protein, firstly characterized as a cyclin dependent kinase (CDK)-inhibitor. Germline CDKN1B pathogenic variants have been described in hereditary tumors, such as MEN-like syndromes and Familial Prostate Cancer. Despite its central role in tumor progression, for a long time it has been proposed that CDKN1B was very rarely somatically mutated in human cancer and that its expression levels were almost exclusively regulated at post-transcriptional level. Yet, the advent of massive parallel sequencing has partially subverted this general understanding demonstrating that, at least in some types of cancer, CDKN1B is mutated in a significant percentage of analyzed samples. Recent works have demonstrated that CDKN1B can be genetically inactivated and this occurs particularly in sporadic Luminal Breast Cancer, Prostate Cancer and Small Intestine Neuroendocrine Tumors. However, a clear picture of the extent and significance of CDKN1B mutations in human malignances is still lacking. Here, we aimed to fill this gap by reviewing the mutational spectrum of CDKN1B in human cancers and the possible impact of these mutations on p27Kip1 protein function and tumor onset and progression.